Late Holocene environmental and climate dynamics along the southern Cape coast of South Africa: high resolution multi-proxy records from the wilderness embayment - du Plessis, Nadia (Department of Environmental and Geographical Science, 2021)
It is well documented that the South African palaeoenvironmental record is relatively limited in terms of both quantity and quality. This is mainly due to the region's highly seasonal rainfall regimes and generally arid to semi-arid environments which are not conducive to the preservation of sedimentary sequences and associated proxy records. The climate along the southern Cape coast is influenced by both tropical and temperate climate systems, and the region hosts highly diverse vegetation including fynbos and thicket elements and includes the Knysna Afrotemperate Region – the most extensive forest complex in southern Africa. The mechanisms controlling these tropical and temperate systems have responded to changing global boundary conditions and these changes have significantly impacted the regional vegetation mosaic. This ephemeral nature of the region's climate and vegetation suggests it is particularly sensitive to climate change, making it an ideal area to evaluate changes in these systems and how they interact over time. For this study, four sets of records were produced from three wetlands along the southern Cape coast. The Eilandvlei palynological and microcharcoal records span the last ~3000 years with the pollen and microcharcoal records from adjacent Bo Langvlei covering the last ~1300 years. The most outstanding feature in these records are the time periods covering the Medieval Climate Anomaly (MCA; c. AD 950 – 1250) and the Little Ice Age (LIA; c. AD 1300 – 1850). The evidence indicates that conditions in the region during the MCA chronozone were relatively dry and perhaps slightly cooler than present. The most durable phase of forest expansion, and likely more humid conditions, occurred during the transition between the MCA and core cooling of the LIA with the LIA clearly identified as a period of cool, dry conditions between c. AD 1600 to c. AD 1850. In addition, the Eilandvlei pollen record demonstrates the effects of external physiographic dynamics on pollen accumulation and deposition within the lake basin. A complementary set of geochemical and sedimentological records have been generated for Bo Langvlei incorporating the last ~4200 years. These records suggest that the late Holocene evolutionary history of Bo Langvlei comprised of three phases: a marine/lagoonal phase extending until c. 1270 cal yr BP, a short transitional phase between c. 1270 and 1200 cal yr BP, and IV the more recent lacustrine phase. A ~650 year pollen and microcharcoal record have been obtained from nearby Vankervelsvlei. Although discontinuous, this is the first palynological record from this unique waterbody covering this period. In terms of climate, the mechanisms driving the observed changes in the records taken as a whole appear to relate to changes in temperature and dynamics in the influence of tropical systems, perhaps transmitted at least in part via the Agulhas Current and the development of localised precipitation systems. The findings further reinforce the proposed importance of summer rainfall in regulating moisture availability along the south coast of South Africa. The records also highlight the significant impacts of fluctuating sea levels and changes in dune morphology in shaping the embayment, and more recently, the effects of accelerated anthropogenic activities in the area